Isolation, serotyping, antimicrobial minimum inhibitory concentration and phatogeneticity determination of erysipelothrixrhusiopathiae from tonsils of apparently healthy slaughter pigs. - Kamaluddin Zarkasie; Toshio Takahashi; Siti Mariana; Sumadi . (Hemera Zoa, 1991)
Erysipolothri rhusiopathiae was isolated from tonsils of 245 (37.5%) of 687 appparently healthy slaughter pigs. Serotyping was performed by an agar gel double diffusion test. Of these 245 isoates, 95 (38.8%) were serotype N, 58 (23.7%) serotype 2, 18 (7.3%) serotype 11, 13 (5.3%) serotype 12, and the remaining 61 isolates were sterotypes 1a, 3, 4, 5, 6, 8, 9, 10, 13, 19 and 22. Antimicrobial Minimum Inhibitiory Concentration (MIC) was determined by two-fold agar dilution test. All isolates were highly suspectible to penicillin G, ampicillin and crythromycin and moderately susceptible to olean domycin, oxytetracyline, chloramphenicol and dihydrostreptomycin and moderately suspectible to oleandomicin, oxytetracyline, chloramphenicol and dihydrostreptomycin. Sulfadimethoxine showed no activity against the isolates. Pathogenicity test showed highly virulent for mica (LD5 0 < 10 3-0 CFU) whereas serotypes 19 and 22 were non-virulent.